The Evaluation of Laser Application in Surgery: A Review Article - khalkhal, Ensieh; Rezaei-Tavirani, Majid; Zali, Mohammad Reza; Akbari, Zahra (Journal of Lasers in Medical Sciences, 2019)
There are several types of surgeries which use lasers in the operating room. Surgeons use lasers in general surgery or surgical specialties to cut, coagulate, and remove tissue. In modern medicine, the application of laser therapy is an attractive subject due to its minimal invasive effect. Today lasers are widely used in the treatment and diagnosis of many diseases such as various cancers, lithotripsy, ophthalmology, as well as dermatology and beauty procedures. Depending on the type of lasers, the wavelength and the delivery system, most lasers have replaced conventional surgical instruments for better wound healing results. Over time, by using many different tools and devices, new lasers have been created; as a result, they are used in a wide range of medical special cases. In this review, laser applications in surgery and its beneficial effects compared to previous surgeries with the aim of providing appropriate therapeutic and non-invasive solutions with minimal side effects after surgery are investigated.